Simulasi Monte Carlo dalam Memprediksi Ketersediaan Barang (PT. Terang Abadi Pekanbaru) - Simatupang, Septian (JURSIMA, 2022)
Abstract Inventory problems not only occur in companies engaged in manufacturing, but the problem also occurs in companies engaged in retail. Inventory problems also occur at PT. Terang Abadi. The inventory system used at this company mostly still uses intuition, estimation, and habits. As a result, predicting inventory becomes very risky when using the simple inventory model. Without a good inventory management, the company will be faced with the risk of being unable to meet customer demand so that inventory analysis needs to be done so that the company does not experience losses. One method that can be used is the monte carlo method. The data taken is inventory data for the last 3 years, namely 2019 to 2021. This data is simulated by programming PHP as a data implementation system. Simulation results from this study obtained an accuracy rate of 90% for simulations in 2019 and 97% for simulations in 2020. By getting greater accuracy, this method is feasible to use and apply to predict the availability of goods in the future. Keywords: Simulation, Monte Carlo, Prediction, Inventory